The influence of Hyssopus cuspidatus Boriss extract on lipid mediators metabolism network in asthmatic mice - Ling-Fei, Kong; Xiao-Juan, Rong; Pan, Yan; Tuo, Qin; Xiao-Hui, Zhang; Yu-Tong, Kang; Bo, Cheng; Wen-Ling, Su; Tian-Le, Gao; Cai, Tie (Frontiers in Pharmacology, 2023)
Current drugs do not provide an absolute cure or modify the course of asthma. Hyssopus cuspidatus Boriss extract (SXCF) has been used as Uyghur medicine for several years to treat bronchial asthma. However, very limited research has been conducted on the therapeutic mechanisms of SXCF. Disruptions in the metabolic network of lipid mediators (LMs) are closely linked to the development of asthma. Here, we explored the therapeutic mechanism of SXCF in asthma based on the metabolic network of LMs, aiming to contribute to the understanding of SXCF in asthma treatment at the molecular level. The UHPLC-MRM strategy was used for the quantitative detection of LMs in the lung tissue and in the peripheral circulatory system (serum). ELISA was used to detect IgE in serum and cytokines in BALF. The lung tissue sections were stained with H&E to observe the infiltration of inflammatory cells, and behavioural changes in mice were observed and recorded throughout the animal experiment. In contrast to the asthma group, the opposite result was observed in the SXCF groups, where the perturbed LMs metabolic network was partly restored in a dose-dependent manner with a significant elevation of anti-inflammatory metabolites, while pro-inflammatory lipids were decreased. As significant downregulation of IgE and pro-inflammatory cytokines was observed, IgE and cytokines analysis also supported the anti-inflammatory effects of SXCF. It was also noticed that SXCF treatment reduced the number of coughs and decreased the inflammatory cell infiltration around the bronchus in mice. These results suggested that SXCF has a significant ameliorative effect on ovalbumin (OVA)-induced asthma. The modulation of LMs is a possible underlying mechanism of the SXCF effects.